Effect of direct-acting antivirals on corrected QT interval and cardiac functions in patients with chronic hepatitis C virus infection - Ibrahim, Mohamed Gamal (Egypt Heart J, 2020)
BACKGROUND: Hepatitis C virus (HCV) infection is a major public health problem in Egypt. The use of direct-acting antivirals (DAAs) in such patients has been shown to be highly effective. The cardiac safety of such antivirals remains uncertain. This study aimed to assess the effect of the novel DAAs on corrected QT (QTc) interval and on cardiac function using trans-thoracic echocardiography. RESULTS: This was a prospective cohort study performed on 100 patients suffering from chronic HCV infection. Patients were into two equal groups according to the presence of liver cirrhosis. The group without liver cirrhosis received a daily combination of sofosbuvir 400 mg and daclatasvir 60 mg for 12 weeks while that with liver cirrhosis (Child-Pugh score A or B) received a daily combination of sofosbuvir 400 mg, daclatasvir 60 mg, and ribavirin 600 mg for 12 weeks. Surface ECG and trans-thoracic echocardiography were performed prior to the start of treatment and after 12 weeks of treatment. At the end of treatment, no changes were observed in QTc interval in those with (p = 0.48) or without (p = 0.048) liver cirrhosis. In patients without liver cirrhosis, right ventricular global longitudinal strain (RV GLS) decreased from 22 (−30 to −17) to −21 (−27–18), p = 0.024. In patients with liver cirrhosis, lateral mitral E’ velocity was reduced from 14.38 ± 3.59 to 13.62 ± 3.21 cm/s, p = 0.02 and indexed left atrial volume (LAVI) was increased from 25.96 ± 3.96 to 26.86 ± 4.12 ml/m(2), p = 0.032. There were no changes in both groups regarding left ventricular (LV) dimensions, ejection fraction, trans-mitral E/A ratio, E/E’ ratio, deceleration time, right ventricular (RV) systolic pressure, mean pulmonary artery pressure, RV fractional area change, tricuspid annular plane systolic excursion, and LV GLS. CONCLUSION: The current national protocol of HCV infection treatment with direct-acting antiviral agents used in Egyptian patients has a good cardiac safety profile. Such treatments have no effect on QTc interval, left and right ventricular functions except for a decrease in RV GLS in those with no liver cirrhosis and a reduction in lateral mitral E’ velocity in those with liver cirrhosis both remained within the normal reference range.